Time‐Dependent Heat Budget of a Thrust from Geological Records and Numerical Experiments. Issue 3 (16th March 2020) - Maino, Matteo; Casini, Leonardo; Boschi, Chiara; Di Giulio, Andrea; Setti, Massimo; Seno, Silvio
Key Points: Thermometric quantification betweenfaulted and undeformed rocks are compared with numerically calculated shearheating during thrusting Distributed cataclastic flow of alarge shallow thrust (5‐7 km depht) produces a persistent temperature incrementof few tens of degrees Higher and more localized temperature increase(50‐150 degrees) requires seismic slip Abstract: We present thermometric measurements and numerical simulations of the thermal budget of a shallow thrust (5–7 km of depth). We determine the temperatures of synkinematic minerals by chlorite geothermometer and illite crystallinity index and sheared veins with stable isotope and fluid inclusion microthemometry. The fault zone attained temperature higher than the wall rocks (ΔT of 50 °C). Some heavily damaged rocks retain a minor but systematic record of a further temperature increase up to 150 °C, and the isotopic signal of fluids indicates a proximal source localized close to the fault zone. We simulated the geological evolution with a suite of elasto‐visco‐plastic thermomechanical models using a 2‐D finite difference code that reproduces the stress, strain, temperature, and pressure variations occurring within the thrust zone. Results indicate that shear heating during distributed cataclastic flow can account for a moderate and persistent temperature increment (ΔT 5–30 °C). Transient higher temperature pulses (50–90 °C) are reproduced simulating coseismic slip along narrow fault planes localized within the broad cataclastic zone. Integration of analytical data and numerical results supports the slow creeping frictional‐viscous deformation as effective mechanism explaining the low‐T part of the thermal history. Seismic deformation equivalent to moment magnitude M w > 6.5–7.0 earthquakes is required to fully account for the thermal signal, including the extreme peak temperature.